Kaitan antara Etnomatematika dan Matematika Sekolah: Sebuah Kajian Konseptual - Sri Wulandari Danoebroto (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
The awareness that mathematics exists at the respective culture needs to be developed in students’ mind through the integration of ethnomathematics at school. School mathematics is different from pure formal mathematics, while ethnomathematics studies pure informal mathematics as well as applied mathematics. This article contains conceptual reviews focused on the comprehension and scope of ethnomathematics, as well as some views on school mathematics to find out the connection between ethnomathematics and school mathematics, also the role of ethnomathematics in school mathematics. The philosophical foundation that connects ethnomatematics and school mathematics is the nature of mathematics as a social construction. Based on this view, it is identified that there are three connections between ethnomatematics and school mathematics, namely ethnomatematics as a learning object of school mathematics, bridge of informal knowledge leading to formal mathematics, and didactic or pedagogical foundations of school mathematics.